Behavioral Responses of Western Flower Thrips (Frankliniella occidentalis) to Visual and Olfactory Cues at Short Distances - Xiaoyun Ren; Shengyong Wu; Zhenlong Xing; Ruirui Xu; Wanzhi Cai; Zhongren Lei (Insects, 2020)
Western flower thrips (WFT), Frankliniella occidentalis (Pergande), is a highly invasive pest, infesting many species of plants worldwide, but few studies have investigated the visual and olfactory cues associated with their foraging behaviors. In this study, the distance traveled by WFT to locate yellow cards using only visual cues and visual cues plus olfactory cues was studied first. Subsequently, preferences for colors (white, red, green, purple, yellow and blue) and patterns (triangle, rectangle, circle and flower-shape) over short distances were assessed with free-choice tests. Finally, as yellow was the most efficient color to catch WFT under laboratory conditions, the yellow flower-shape was used as the visual cue, and preferences between visual and olfactory cues were evaluated with dual choice tests. The results showed that the capture rate of WFT by visual cues decreased as selection distance increased, however capture rate remained higher with the addition of olfactory cues. The flower shape attracted the greatest number of WFT among all shapes tested. The combination of visual cues and extracted volatiles from flowering Medicago sativa L. attracted higher numbers of WFT than to the olfactory cues alone, however these were similar to visual cues alone. The presence of olfactory cues resulted in higher residence times by WFT than did the absence of olfactory cues. These results show the relative effects of visual and olfactory cues on the orientation of WFT to hosts and highlight that visual cues dominate selection behavior at short distances. These findings can be used in the development of efficient trapping products and management strategies for thrips.